Seroprevalence of SARS-CoV-2 IgM and IgG antibodies in an asymptomatic population in Sergipe, Brazil - Borges, Lysandro Pinto (Rev Panam Salud Publica, 2020)
OBJECTIVE. To estimate the prevalence of SARS-CoV-2 antibodies in an asymptomatic population in the state of Sergipe, Brazil.  METHODS. This cross-sectional study with stratified sampling (sex and age) included serological immunofluorescent tests for IgM and IgG on samples from 3 046 asymptomatic individuals. Sample collection was performed in wet-markets of the 10 most populous cities of Sergipe, Brazil. Exclusion criteria included symptomatic individuals and health workers. The presence of comorbidities was registered.  RESULTS. Of the 3 046 participants, 1 577 (51.8%) were female and 1 469 (48.2%) were male; the mean age was 39.76 (SD 16.83) years old. 2 921 tests were considered valid for IgM and 2 635 for IgG. Of the valid samples, 347 (11.9% [CI 10.7%–13.1%]) tested positive for IgM and 218 (8.3% [CI 7.2%–9.4%]) tested positive for IgG. Women over 40 had the highest prevalence for IgM (group C, p=0.006; group D p=0.04). The capital Aracaju displayed the highest prevalence for both antibodies; 83 (26.3% [CI 21.6%-31.6%]) tested positive for IgM and 35 (14.6% [CI 10.4%-19.7%]) for IgG. The most prevalent comorbidities were hypertension (64/123 individuals) and diabetes (29/123).  CONCLUSIONS. A high prevalence of SARS-CoV-2 antibodies was found among asymptomatic persons in Sergipe. Women over 40 showed the highest rates. The capital, Aracaju, displayed the highest seroprevalence. Surveys like this one are important to understand how the virus spreads and to help authorities to plan measures to control it. Repeated serologic testing are required to track the progress of the epidemic.